Methods and difficulties of different ways in gaining central line access: a literature review - Alkholy, Muhammad A.; Albarakati, Jumanah T.; Rawas, Mustafa M.; Rayes, Lujain O.; Alghamdi, Manal A.; Naaman, Belal; Alyamani, Wejdan A.; Alqahtani, Awadh M.; Alrashidi, Sultan S.; Amin, Amin A.; Alyahyawi, Talal S. (International Journal Of Community Medicine And Public Health, 2021)
The central line is one of the vital techniques in medicine and it is widely used for critically ill patients’ resuscitation. Proper knowledge of the proper techniques and understanding how to choose the perfect central vein for each patient is considered a vital skill for physicians. In this study, we reviewed the literature to provide a simple guide for physicians. PubMed, Medline, Web of Science, Embase, Google Scholar, and Scopus using the following search terms (“Central line” or “central catheter”) and (“method” or “procedure” or “complication”). We included any study that reports the methods and difficulties of different ways of gaining central line access. Based on our results, the proper choice of the central line and the site of insertion are the determining factors for the success of the procedure and decreasing the risk of complications. The ultrasound-guided approach is considered the best option to avoid any injury of the vital structures.